Natural restoration of mechanical properties of concrete subjected to high temperature. Issue 1 (22nd December 2017) - Li, Qingtao; Pang, Haolei; Yuan, Guanglin
Abstract : The effects of heating temperature, cooling method, re-curing time and water-to-cement ratio ( w/c ) on the natural restoration of mechanical properties of concrete exposed to high temperature were experimentally studied. The fire-damaged concrete specimens were re-cured in ambient conditions after they had been rapidly cooled in water and naturally cooled in air. Below 500°C, the natural restoration of the compressive strength of water-cooled concrete was more evident than that of air-cooled concrete. The natural restoration of the compressive strength of air-cooled concrete with low w/c ratio was more obvious than that of concrete with high w/c ratio. After being subjected to 500°C and re-cured for 3 months, the splitting tensile strength decreased to below 26% of the initial value. The splitting tensile strength of water-cooled concrete recovered more evidently than that of the air-cooled concrete. The restoration of elastic modulus was mainly affected by the heating temperature and cooling method. The elastic modulus of water-cooled concrete which had been subjected to 200, 300 and 400°C was obviously restored after being naturally re-cured for 3 months. The effects of w/c on the tensile strength and elastic modulus were not significant.